Cardiac structure and function in veteran recreational endurance athletes. (3rd October 2022) - Sorensen, E; Myrstad, M; Oie, E; Solberg, M G; Tveit, A; Aaronaes, M
Abstract: Background: Even though physical activity is inversely associated with cardiovascular disease, long-term endurance exercise increases the risk of AF in middle-aged and older men, and has been linked to cardiac structural changes mimicking arrhythmogenic cardiomyopathy on susceptible individuals. Healthy younger athletes adapt to the increased demands of exercise with symmetric enlargement of the cardiac chambers with preserved functional properties. Data describing cardiac structure and function in older veteran athletes after decades of performing endurance exercise are scarce and add essential information when wanting to discern physiological from pathological remodeling in this group. Purpose: To investigate cardiac structural and functional remodeling in relation to long-term endurance exercise in veteran athletes. Methods: To cover the entire range of physical activity in the population, the study comprised two independent cohorts; Veteran male athletes who had participated in the annual 54 km Birkebeiner cross-country ski race and men who had participated in a population-based health survey. Individuals with a history of cardiac arrhythmias were excluded. Regular endurance exercise was defined as exercise for ≥30 minutes at least three times weekly with the purpose of increasing physical endurance capacity and self-reported as categories of years of regular endurance exercise. All participants underwent a resting echocardiographic examination. A One-way ANOVA with polynomial contrasts was conducted to explore the effect of years of endurance exercise on cardiac size and function. Results: 178 men with a mean age of 70.9±6.5 years were included in the study, 89 veteran athletes, who had practiced regular endurance exercise for an average of 40–50 years, and completed an average of 19 annual Birkebeiner ski races and 89 individuals from the general population. Fifty-seven had never performed regular endurance exercise, 29 1–20 years of exercise, 25 20–40 years of exercise, and 67 >40 years of endurance exercise. Left atrial, left ventricular, right atrial, and right ventricular dimensions increased with cumulative years of exercise (p<0.001), while function remained similar in all cardiac chambers. Conclusion: Atrial and ventricular dimensions increased with cumulative years of endurance exercise. Atrial and ventricular function assessed by strain, however, seemed to be unaffected by long-term exposure to exercise. These results suggest recreational endurance athletes preserve normal cardiac function despite athletic remodeling. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): A Ph.D. grant from the DAM foundationA grant from the Raagholt foundation